Retensi Karyawan pada Usaha Kecil: Studi Eksploratori pada Klaster Usaha Kecil Menengah (UKM) Pengolahan Logam di Kebasen, Tegal - Martdianty, Fanny (Jurnal Manajemen dan Usahawan Indonesia, 2020)
This study aims to determine the factors that influence voluntary turnover and how owners/ man- agers in SMEs conduct retention on their employees because the studies related to HR management in SMEs are still relatively few. Data was collected through semi-structured interviews with five own- ers /SME managers and 19 employees from five metal processing SMEs in Kebasen, Tegal. From the results, some findings based on employee information revealed that the reasons for employees leaving were mainly related to compensation issues and the intention to open a similar business. Whereas from the owner/ manager’s perspective, the reason employees leaving are: dissatisfaction with wages, employee hijacking (poaching), and personal problems. For matters relating to factors that can re- tain employees include: family culture, relationships both with superiors and coworkers as well as the flexibility offered by SMEs.